#TITLE_ALTERNATIVE# - RIZKY PAHLEVY (NIM : 12214025), MOHAMAD
Gas lift is an artficial lift method commonly used in the petroleum industry which aims to increase the production rate at wells with relatively low reservoir pressure as well as on wells that can not flow naturally. To increase the production of a gas lift well, it is necessary to identify problems which later can be made some recommendations to those problems, this is very important to do, considering that the wells to be conducted have more optimum production potential. This study concludes that to increase the yield of oil in gas lift well, sensitivity to factors affecting production rate is needed to maximize the production of a well. Design of gas lift wells can be done by doing sensitvity rate of injection to get gas lift performance curve which is useful to determine how the rate of injection gas rate is the most optimum, then the sensitivity of the tubing size at the well with nodal analysis by making Vertical Lift Performance (VLP) curves vs Inflow Performance relationship (IPR) curves with different tubing size variables to obtain the optimum tubing size. Then, determining the depth of the injection point, the deeper gas is injected into the well then the production rate will increase but the higher compressor pressure is required. The next step is spacing design analysis to get the location of the unloader and orifice for unloading and injection process. Finally, force balance calculation method is used to find out the amount of pressure that works on the valve at the time of unloading and operating. The calculation of the pressure acting on the valve is carried out at the process of displacemet killing fluid and at the time of gas injection operation.